Change Management in Oncology Nursing Practice - Tsatsou, Ioanna (Journal of Current Health Sciences, 2025)
Oncology nursing operates within a rapidly evolving environment, driven by continuous innovations in medical treatments, technology, and organizational processes. Effective change management is critical for maintaining quality patient care, enhancing staff satisfaction, and ensuring operational efficiency. This paper explores theoretical foundations of change management, specifically examining Lewin’s Change Theory and Kotter’s 8-Step Model, and their applicability in oncology nursing contexts. Structured frameworks provided by these theories facilitate the integration and sustained adoption of innovative clinical practices. Additionally, this review assesses implications of structured change management for clinical nursing practice and healthcare leadership. It emphasizes the critical role nursing leaders play in advocating for and implementing change through clear communication, staff empowerment, and transformational leadership practices. Finally, the paper identifies future research directions, highlighting the importance of evaluating long-term impacts of change management strategies, particularly regarding advanced technologies such as artificial intelligence and precision medicine, nurse job satisfaction, and patient care outcomes. This comprehensive analysis underscores the necessity of structured change management to foster resilience, minimize burnout among oncology nurses, and ultimately enhance patient-centered care delivery in oncology settings.